Role of Nd3+ nanoparticles on enhanced optical efficiency in borotellurite glass for optical fiber - Abd Azis, Muhammad Noorazlan; Mohamed Kamari, Halimah (Elsevier, 2018)
The main problem of commercial silicate glass fiber is its high-loss and weak optical efficiency. It is very important to produce non-silicate glass fiber with low-loss and high optical efficiency. In this work, low-loss and high optical efficiency of Nd3+ nanoparticles doped borotellurite glass had been produced. The analysis of FTIR spectra shows the presence of functional vibration of tellurite network. The refractive index of borotellurite glass was enhanced in between 1.947 and 2.045 with the increment of Nd3+ nanoparticles. Several excitation bands within UV–Vis range due to the effect of Nd3+ nanoparticles was perceived originating from the ground state 4I9/2 to the excited states 2P3/2, 4G7/2, 4G5/2, 4F9/2, 4F7/2, 4F5/2 and 4F3/2. The glass system shows tendency towards semiconducting behavior as the value of Fermi energy, EF decreases. The high intensity of red emission was found from Nd3+ nanoparticles doped borotellurite glass. Hence, this Nd3+ nanoparticles doped borotellurite glass has immense potential for the development of fiber amplifiers and lasers.